BRAF V600E Mutation in Odontogenic Keratocyst: A Systematic Review and Meta-Analysis - Jéssica da Silva Cunha; Lucas Nascimento Ribeiro; Allan Vinícius Martins-de-Barros; Raisa Jordana Geraldine Severino-Lazo; Raíssa Soares dos Anjos; Renata de Albuquerque Cavalcanti Almeida; Mohammed N. Islam; Marianne de Vasconcelos Carvalho (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To assess the frequency of the BRAF V600E mutation in odontogenic keratocyst, correlating the methods of evaluation and detection of the mutated protein. Material and Methods: This systematic review was conducted following the PRISMA guidelines and registered in PROSPERO (CRD 42022379570). An electronic search was performed up to January 20th, 2024, in the databases of Medline, Scopus, Embase, and gray literature (Google Scholar, BDTD). One hundred and sixty-six cases in seven studies were included. The methodological quality of the studies was performed according to the Joanna Briggs Institute. Results: Only two of the seven studies reported positivity for the BRAF V600E mutation, both by molecular methods. In the remaining five studies, the BRAF V600E mutation was not present, one evaluated by RT-PCR, three by DNA sequencing, and one by IHC. Conclusion: Through analysis of the articles, the BRAF V600E gene mutation alone does not play a significant role in the pathogenesis of OKC. Further research and new studies are necessary.